Chemopreventive role of olive oil in colon carcinogenesis by targeting noncoding RNAs and methylation machinery. Issue 5 (4th October 2018) - Nanda, Neha; Mahmood, Safrun; Bhatia, Alka; Mahmood, Akhtar; Dhawan, Devinder Kumar
Abstract : Epigenetic therapy induced by dietary components has become a strong interest in the field of cancer prevention. Olive oil, a potent dietary chemopreventive agent, control colon cancer, however, its role in epigenetic therapy remains unclear. Thus, we aimed to investigate the effect of olive oil in a preclinical model of colon cancer by targeting genetic and epigenetic mechanisms. DMH was used to induce colon cancer in rats; while olive oil was given to separate group of rats along with DMH treatment. Tumor burden and incidence in DMH and DMH + olive oil‐treated rats was observed by macroscopic examination and histoarchitectural studies. Potent anti‐inflammatory, anti‐angiogenic and pro‐apoptotic activity of olive oil was explored by gene expression and immunohistochemical studies. The effect of olive oil on epigenetic alterations was examined by detecting promoter methylation with MS‐HRM and dysregulation of miRNA by TaqMan MicroRNA Assay. We observed that olive oil administration lowered tumor incidence and inhibited the development of tumors in DMH‐treated rats. Olive oil markedly decreased the expression of inflammatory and angiogenic markers and restored the expression of pro‐apoptotic markers in DMH‐treated rats. Furthermore, the inverse relationship between gene expression and DNA methylation, deviant miRNA pattern and miRNA silencing mediated by aberrant DNA methylation was also seen in DMH‐treated rats, which was potentially reversible upon olive oil treatment. Our study concludes that olive oil may play a role in the epigenetic therapy by altering NF‐κB and apoptotic pathways via targeting noncoding RNAs and methylation machinery that affecting epigenome to prevent colon carcinogenesis. Abstract : What's new? Epigenetic therapy induced by dietary components has strong potential in cancer prevention. Olive oil presents some chemopreventive activity in colon cancer, but its potential role in epigenetic therapy remains unclear. This study shows that olive oil prevents colon cancer by reducing the expression of inflammatory and angiogenic genes and enhancing apoptotic genes and miRNAs expression in a preclinical model. Moreover, the interface between DNA methylation and miRNA expression associates with transcriptional silencing of genes encoding for altered cellular pathways in colon cancer. Olive oil acts as a demethylating agent for tumor suppressor genes and hypermethylating agents for tumor promoter genes.